An Ethnobotanical Study of Medicinal Plants Used for the Treatment of Gout by the Community of Bandung City - Hasna Nabila; Arie Aryanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Gout is a metabolic disorder characterized by elevated uric acid levels that can cause inflammation and joint pain. In recent years, the incidence of gout has increased, including among younger populations, highlighting the need for alternative and complementary treatments. This study aimed to explore the ethnobotanical knowledge of medicinal plants used by the community of Ujungberung District, Bandung City, in the management of gout. This research employed a qualitative ethnobotanical approach. Data were collected through in-depth interviews, participatory observation, and literature review involving 20 selected informants using purposive sampling. The study was conducted from December 2025 to January 2026. The results identified nine medicinal plant species commonly used to treat gout, with ginger, turmeric, and bay leaf being the most frequently utilized. The plants were mainly processed by boiling, and their use was based on traditional knowledge passed down through generations. These plants contain bioactive compounds such as flavonoids, curcuminoids, and essential oils, which are known to have anti-inflammatory and uric acid–lowering properties. In conclusion, the community in Ujungberung District continues to rely on medicinal plants as a complementary therapy for gout management. This study emphasizes the importance of documenting ethnobotanical knowledge and highlights the potential of local medicinal plants as accessible and affordable alternatives for gout treatment.